การพัฒนาพันธุ์กุหลาบสีน้ำเงินและมะเขือเทศสีม่วงโดยใช้เทคนิคทางพันธุวิศวกรรม: The Development of “Blue Rose” and “Purple Tomato” by Genetic Engineering Techniques - Klanrit, Preekamol (Asian Health, Science and Technology Reports, 2010)
Anthocyanins are members of a flavonoid class of natural pigments synthesized by plants, which are responsible for most light yellow, blue, purple or red colors found in many flowers and fruits. This attractive characteristic contributes to seed dispersal by a variety of insects and animals. In addition, anthocyanins have antioxidant and anti-cancer properties, which are considered potential health benefits for human. According to the previously mentioned characteristics, more researches have been focused on plant improvements to be able to synthesize flavonoids especially anthocyanins. This review presents the applications of genetic engineering to create a novel purple/blue rose and purple tomato, which are based on similar concepts. The process begins with the cloning of genes encoding the enzymes responsible for the synthesis of delphinidin-based anthocyanins, which can be groups of genes working together, and the origins of the genes can come from different plant species. Then, the sets of genes have to be transformed into the plants, selection of transgenic lines, and finally the plant tissue culture is employed to regenerate the whole new genetically modified plants.